Palladium‐Catalyzed Carbonylative Homocoupling of Aryl Iodides for the Synthesis of Symmetrical Diaryl Ketones with Formic Acid. Issue 1 (21st November 2017) - Wu, Fu‐Peng; Peng, Jin‐Bao; Qi, Xinxin; Wu, Xiao‐Feng
Abstract: A convenient method for the palladium‐catalyzed carbonylative homocoupling of aryl iodides was developed. With formic acid as the CO source, various symmetrical diaryl ketones were synthesized in moderate to good yield in the presence of a palladium catalyst. Abstract : Setting the ke‐tone : A convenient method for the palladium‐catalyzed carbonylative homocoupling of aryl iodides is developed. By using formic acid as the CO source, various symmetrical diaryl ketones can be produced in moderate to good yields. DPEphos=bis[(2‐diphenylphosphino)phenyl] ether, DCC= N, N ′‐dicyclohexylcarbodiimide.